STUDENT'S READING COMPREHENSION IN NARRATIVE READING TEXT AT SMK SANDI PUTRA 2 MEDAN - GINTING, PERNANDO KENJIRO; nissa, Chairun (ELT (English Language Teaching Prima Journal), 2022)
This research was conducted to describe students' abilities in reading and understanding narrative texts. The purpose of this study was to analyze students' ability to understand narrative texts. This method uses a qualitative descriptive method. This research was conducted at SMK Telkom 2 Medan. There were 30 students in class X, this study used two types of instruments, namely tests and interviews.Based on the results of the research, it was found that the highest student score was 85 and the lowestscore was 55. The low student score was caused by a lack of vocabulary, did not understand words, and found difficult words Keyword: Reading Comperhasion, Narrative Text,Reading Narrative Text